Transcutaneous auricular vagus nerve stimulation for long-term post-stroke cognitive impairment: a DTI case report - Chen, Xixi; Zhou, Zhiqing; Chong, Kayee; Zhao, Jingjun; Wu, Yuwei; Ren, Meng; Huang, Yu; Chen, Songmei; Shan, Chunlei (Frontiers in Human Neuroscience, 2024)
Purpose: Long-term post-stroke cognitive impairment (PSCI) exhibits an accelerated rate of long-term cognitive decline, which can impair communication, limit social engagement, and increase rate of institutional dependence. The aim of this case report is to provide evidence for the potential of home-based transcutaneous auricular vagus nerve stimulation (taVNS) for home-bound patients with severe, long-term PSCI.Methods: A 71-year-old male suffered a stroke two and a half years ago, which imaging reported foci of cerebral infarction visible in the left temporal and parietal lobes. The patient was performed taVNS twice a day for 30 min, 5 times a week for 8 weeks. The patient was evaluated the changes of cognitive function and brain white matter at 4 time points: baseline (t0), 4 weeks 2 without taVNS after baseline (t1), 4 weeks of intervention (t2), and 8 weeks of intervention (t3).The effect of taVNS on white matter changes was visualized by DTI.Results: After 8 weeks of taVNS treatment, the scores of Montreal cognitive assessment improved and the time to complete the shape trails test decreased. The DTI results showed that white matter in bilateral dorsal lateral prefrontal cortex remodeled after taVNS.Eight-week home-based taVNS may be beneficial to long-term PSCI. Further studies of home-based taVNS treating patients with long-term PSCI are needed.